Clinical Update: The Implementation of Evidence-Based Emotion Regulation Treatment for Clients with Autism. Issue 1 (2nd January 2021) - White, Susan W.; Conner, Caitlin M.; Beck, Kelly B.; Mazefsky, Carla A.
ABSTRACT: Autism is more widely recognized and diagnosed than ever before, due in part to broadened diagnostic criteria, heightened awareness of the condition in popular media, and improved early identification. Difficulty with managing intense emotion is common among children and adolescents with autism spectrum disorder (ASD). Impaired emotion regulation (ER) often leads to clinic referral and crisis situations. This clinical update was prompted by multiple requests from providers, and pleas from parents, for guidance on how to best manage ER difficulties in children and adolescents with ASD. In this article, we summarize the nature of ER problems in ASD, provide a synthesis of the treatment research in this area, and provide suggestions for clinicians who do not necessarily specialize in ASD but may get referrals of this nature. It is our view that many mental health clinicians possess the competence to utilize evidence-based interventions to treat ER problems, and need training only on individualizing treatment for clients with ASD, to better meet the needs of this growing patient group.